2017
DOI: 10.1111/idh.12282
|View full text |Cite
|
Sign up to set email alerts
|

Change in oral health status associated with menopause in Japanese dental hygienists

Abstract: The results demonstrated a negative correlation between E2 levels and SRQ-D scores as well as salivary α-amylase activities, suggesting an influence of E2 on mental condition. Furthermore, E2 decrease may result in reduction of salivary flow which in turn causes various problems of oral health. Since the participants were graduates from several dental hygienist schools and working at various places, these results can be generalized to Japanese dental hygienists to some extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
2
13
1
3
Order By: Relevance
“…5,8,9 Based on the comparison of salivary rates among women in premenopausal and postmenopausal periods, it was found that postmenopausal women presented lower non-stimulated salivary flow. 26 These findings suggest that intervention studies are important for the implementation of measures of prevention and comfort for women in the postmenopausal period.…”
Section: Use Of Continuous Medications Nomentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,9 Based on the comparison of salivary rates among women in premenopausal and postmenopausal periods, it was found that postmenopausal women presented lower non-stimulated salivary flow. 26 These findings suggest that intervention studies are important for the implementation of measures of prevention and comfort for women in the postmenopausal period.…”
Section: Use Of Continuous Medications Nomentioning
confidence: 99%
“…The continuous use of drugs associated with xerostomia and salivary gland hypofunction has been described by different methodological approaches in the literature 5 ; nevertheless, it is known that polypharmacy and the use of specific medications play a crucial role in salivary gland hypofunction. 9,16 Among these medications, diuretics 5,26 and antidepressants are the most harmful to salivation. 27 This corroborates the literature, showing that the continuous use of medication impacts on the prevalence of xerostomia in the older persons, and on hypofunction of the salivary gland when stimulated.…”
Section: Use Of Continuous Medications Nomentioning
confidence: 99%
“…Here, periodontal disease was divided into gingivitis and periodontitis, based on previous studies reporting differences in bone density and attachment loss according to changes in hormones related to menopause 7,16,17) , and we aimed to establish basic data that will be necessary for setting up policies for the prevention of periodontal disease and improvement of oral health for women in menopause.…”
Section: Discussionmentioning
confidence: 99%
“…However, postmenopausal hormone imbalances also have an impact on oral quality of life: a very recent cross-sectional study of 97 female dental hygienists (age 40-59) assessed personal wellbeing and correlated it with oral and systemic parameters: estrogen deficiency in blood serum was correlated with decreased salivation and higher depression scores [12]. the mouth", sometimes representing as mucosal redness or erosion.…”
Section: Definitions and Biological Backgroundmentioning
confidence: 99%